(untitled) (Global Journal of Science Frontier Research, 2015)
A quantum paradox of nonlocal Einstein-Podolsky-Rosen correlation between counterpropagating pair of polarization-entangled photons emitted from a common source S and detected at points P and Q is solved outside the EPR’s reality criterion of local causality but within the framework of time-symmetric quantum electrodynamics allowing the bi-directional signal transmission P↔S↔Q on the double-light cone where the future and the past cones. share common light paths connecting the photon source S and the detection points P and Q. A cosmlogical implication of the bi-directional signal transmission P↔Q without common source S in cosmology and possible Planckeon orgin of dark energy in the upper hemisphere of semiclosed Friedman uiverse, joined on to an asymptotically flat outer space, are also discussed.